"Scribble Scrabble": Migration, Young Parenting Latinas, and Digital Storytelling as Narrative Shock. (21st May 2019) - Krause, Elizabeth L.; Gubrium, Aline C.
Abstract: The nexus of migration and family offers a conjuncture to enrich understanding of teen pregnancy and parenting. This article draws findings from a project centered on participant‐produced new media to reveal how young mothers negotiate reproductive health disparities. We focus on young mothers' experiences of migration and movement, captured in local vernacular through participants' digital story depictions and follow‐up interviews. We argue that disparities link up with the single story of teen mothering, involve public shaming, continue hand‐in‐hand with institutional humiliation, and are exacerbated through migration and movement. To disrupt the normative notions that shadow young mothers, we take seriously the young women's narratives. We theorize how the richness of stories and storytelling may serve as a potent intervention—a narrative shock—for articulating meanings and cultivating dignity for young mothers and their families, especially those who do not fit the sedentary and age biases of parenting ideals.